EFFECT OF CRYOPROTECTANTS AND CRYOPRESERVATION METHODS ON THE QUALITY OF BUFFALO OOCYTES - H T A., Alkhazraji; H J H., Banana; M-BM R.,Fakhrildin (The Iraqi Journal of Agricultural science, 2023)
This study was conducted to evaluate the effect of two types of cryoprotectants and two cryopreservation methods on viability and normal morphology of the immature and in vitro mature of post-thawed buffalo oocytes. The in vitro mature and immature oocytes were kept in the vitrification solution (VS1) for 5 min and the vitrification solution (VS2) for 15 sec. The results revealed that the proportion of buffalo oocytes found to be viable and normal morphology were significantly (P< 0.01) higher in using glycerol which is 76.14% and 55.1%; respectively. We conclude from the present study that the viability and normal morphology of post-thawed buffalo vitrified in vitro matured oocytes were significantly (P < 0.01) higher in glycerol than those obtained in dimethyl sulfoxide (DMSO) and in vitrification technique than rapid technique.